STATISTICAL METHOD OF DIAGNOSTIC DEFECTS OF PRODUCTS OF COMPOSITES - Єременко, В. С.; Сунетчієва, С. Р. (Science-based technologies, 2014)
Acoustic impedance method is one of the most popular ways in non-destructive testing of compounds in multilayer structures. The method is based on difference of mechanical impedances in damaged and defect-free areas of controlled product. The main informative parameter for most contemporary flaw detectors is the amplitude of the signal, received from the impedance sensor. Usually diagnostic decision making is based on threshold overrunning by chosen informative parameter. Threshold value can be calculated with the help of statistical methods that include information about the distribution law of informative parameters samples obtained from and defect-free areas. For evaluating the possibility of choosing approach for the approximation of the laws of distribution of information parameter, we have done the experimental testing of composite samples with artificially marked defects. Tables 1 and 2 present the results of the research. The proposed criterion consent can be used to identify defect of products with an unknown distribution law.